The influence of the atmospheric front on the readings of the gravimeters and seismographs - Yu. V. Antonov (Известия высших учебных заведений: Геология и разведка)
Non-tidal variations of gravity are the residual part of the monitoring of the variations after subtraction from them the lunar-solar gravity variations and the drift of the zero point of the gravimeter. Non-tidal variations have a complex morphology and structure. The sources of the non-tidal variations are the intracrustal processes, flows of the charged particles in space and meteor showers. Meteor showers interacting with the Earth’s atmosphere determine the occurrence, development and movement in the atmosphere of the large-scale eddies - cyclones and anticyclones. The atmospheric fronts are distinguished in isolated cyclones. These fronts can influence the measurements of the gravimeters and seismographs.